2020
DOI: 10.1111/trf.16034
|View full text |Cite
|
Sign up to set email alerts
|

RH genotyping by nonspecific quantitative next‐generation sequencing

Abstract: Background: Conventional sequencing uses gene-specific primers to determine the location of RH variants and permits a qualitative assessment of zygosity. Whole-genome and whole-exome sequencing determine the genetic location of variants and enable a quantitative assessment of zygosity. Nonspecific sequencing uses RH-consensus primers to detect variants and sequencing-read ratios to quantify their copy number. Study Design and Methods: Two hundred seventy eight samples with diverse genotypes were analyzed by ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…We chose 27 rs positions encoding BG/HPA antigens and markers for creating the Ion AmpliSeq HD designer custom ordered gene panel. Twenty‐five ROIs were applied; however, primers for the rs676785 and rs7682260 used by Wienzek‐Lischka et al, for RhC/c and M/N antigens, respectively, were reported not to be included due to high homology to other regions 18,19 . The Ion AmpliSeq HD panel improved the efficiency of the HPA‐5 sequencing, while the reactions for the GYPB gene had a lower yield compared with other ROIs (Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose 27 rs positions encoding BG/HPA antigens and markers for creating the Ion AmpliSeq HD designer custom ordered gene panel. Twenty‐five ROIs were applied; however, primers for the rs676785 and rs7682260 used by Wienzek‐Lischka et al, for RhC/c and M/N antigens, respectively, were reported not to be included due to high homology to other regions 18,19 . The Ion AmpliSeq HD panel improved the efficiency of the HPA‐5 sequencing, while the reactions for the GYPB gene had a lower yield compared with other ROIs (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five ROIs were applied; however, primers for the rs676785 and rs7682260 used by Wienzek-Lischka et al, for RhC/c and M/N antigens, respectively, were reported not to be included due to high homology to other regions. 18,19 The Ion AmpliSeq HD panel improved the efficiency of the HPA-5 sequencing, while the reactions for the GYPB gene had a lower yield compared with other ROIs (Table S1). Considering the detection of RHD gene, it is known that the real-time PCR technique is a gold standard for fetal RHD typing for immunized RhDnegative women and targeted antenatal immunoprophylaxis in non-immunized mothers, so there is no need to convert a test into other expensive technique.…”
Section: Rh(eàe+mentioning
confidence: 99%
“…Current research on the distribution of variant RHD alleles has been mostly focused on European donor and patient cohorts (10)(11)(12)(13)(14). Additionally, there are some corresponding reports on the diversity of RHD alleles in African and Asian populations (15).…”
Section: Introductionmentioning
confidence: 99%
“…We propose that blood antigen interpretation is a universal clinical benefit that could increase the cost‐efficiency of genomic sequencing performed in the clinical setting [14]. To this end, important challenges involve design and validation of bioinformatic pipelines tailored to evaluate blood antigen expression and compatibility, and automation suitable for application to a large number of donor and recipient genomes [13,15–21].…”
Section: Introductionmentioning
confidence: 99%